PENGARUH GAYA KOMUNIKASI ORANGTUA TERHADAP KECERDASAN INTERPERSONAL ANAK USIA DINI - Nurhasanah Nurhasanah; Inten Risna; Devi Ayu Kurniawati; Ratu Yustika Rini; Galuh Mulyawan (Jurnal Manajemen Pendidikan, 2026)
The development of interpersonal intelligence in early childhood is a crucial aspect of shaping social and emotional competencies that support children's future success. This study aims to examine the influence of parental communication style on the interpersonal intelligence of early childhood students at PAUD Al-Mizan, Serang City. This research employed a quantitative approach with a correlational design. The sample consisted of 30 parents selected using a saturated sampling technique. Research instruments included a parental communication style questionnaire and an interpersonal intelligence questionnaire containing several indicators. Data analysis involved a linearity test, Pearson Product Moment correlation, and a t-test to determine the significance of the influence. The results indicated that parental communication style was generally in the moderate to high category, and children’s interpersonal intelligence also fell within the same range. The correlation test revealed a positive and significant relationship between parental communication style and children's interpersonal intelligence, with an r value of 0,361 (p < 0,05). The t-test further confirmed a significant influence, showing a t value of 3,205 greater than the critical value of 2,048 and p = 0,003. These findings conclude that parental communication style plays an essential role in fostering interpersonal intelligence in early childhood.